Analisis eksploratori dana masjid di negeri Perak - Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Abdul Razak Azila, Habidin Nurul Fadly, (N/A, 2014)
Analisis eksploratori dana masjid di negeri Perak by Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Abdul Razak Azila, Habidin Nurul Fadly,